Predictors and Long-Term Clinical Outcome of Longitudinal Stent Deformation: Insights From Pooled Analysis of Korean Multicenter Drug-Eluting Stent Cohort. (November 2017) - Rhee, Tae-Min; Park, Kyung Woo; Lee, Joo Myung; Lee, Michael S.; Jeon, Ki-Hyun; Kang, Hyun-Jae; Koo, Bon-Kwon; Rhew, Jay Young; Cha, Kwang Soo; Bae, Jang-Ho; Han, Kyoo-Rok; Park, Si-Hoon; et al.
Abstract : Background—: There are limited data on the frequency of and factors associated with quantitative coronary angiography (QCA)–defined longitudinal stent deformation (LSD) in various contemporary drug-eluting stents platforms. This study sought to evaluate the predictors of LSD and its long-term clinical implication. Methods and Results—: A patient-level pooled analysis was performed with 7350 lesions in 5871 patients treated with platinum-chromium–based everolimus-eluting stent (Promus Element), cobalt-chromium–based everolimus-eluting stent (Promus/Xience V), or cobalt-chromium–based zotarolimus-eluting stent (Endeavor Resolute). QCA was performed to analyze differences of stent length between immediate post-deployment and final post-procedure. Independent factors associated with LSD were identified. Clinical outcomes at 3 years were compared between those with and without QCA-based LSD. The frequency of QCA-based LSD was 1.12% (82 cases). Nine of these cases were angiographically overt. Left main or ostial lesion, bifurcation treatment with provisional side branch stenting or ballooning, additional downstream intervention of a distal lesion, intravascular ultrasound use, and adjunctive post-dilatation were independently associated with QCA-based LSD. The type of stent was not associated with QCA-based LSD. Rates of target lesion failure were nominally higher in lesions with QCA-based LSD than in those without (8.97% versus 5.88%; hazard ratio, 1.415; 95% confidence interval, 0.631–3.175; P =0.399). Conclusions—: LSD is uncommon with contemporary drug-eluting stents, regardless of the type of stent platform. LSD is mainly associated with procedural factors, especially with additional downstream procedures which require the passage of devices through the stent. Careful manipulation of poststent imaging or procedural devices is required to prevent LSD. More data are needed to clarify the impact of LSD on clinical events. Abstract : Supplemental Digital Content is available in the text.